The Sporadic Customary Land Registration Problems - Laksmana, Gustav Tifa; Maryanto, Maryanto (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This research is aimed at the majority of the population of the Gubug District community, which has not yet obtained a land certificate. Because they still don't understand the meaning and function as well as land certificates, so the proof of land ownership uses the Village C/D letter. Based on Government Regulation Number 24 of 1997 concerning Land Registration, this Government Regulation is the basis for conducting land registration. However, in reality there are still many who have not carried out the certification process. The problems studied are: the problems of sporadic implementation of customary land registration, obstacles and efforts in the implementation of land registration. The approach method used in this study is an empirical or sociological juridical approach. While the data analysis method used in this study is a qualitative method. Based on the results of the study, it shows that the process of implementing customary land registration has not been carried out in part by a sporadic system at the Land Office and PPAT and in the implementation there are still obstacles that are still considered difficult and expensive, the cost of land registration certificates and ignorance in the community. Meanwhile, the solution sought is to provide information and socialization so that the community understands more about the importance of land certificates.